Clerodendrum inerme (L.) Gaertn. Extract Exerts Anticancer Activity on Lung Cancer Cells - Chouhan, Mahendra Kumar; Hurakadle, Pramod Jayadevappa; Hegde, Harsha Vasudev (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Cancer is the leading cause of death word wide. Recently there are no new drugs for safe and efficient treatment. Clerodendrum inerme (L.) Gaertn. (Verbenaceae) plant is being used by the ethnic people for cancer treatment. In this study, cytotoxic and antiproliferative potential of hydroalcoholic (methanol and water; 70:30 v/v) extract of C. inerme were evaluated. Various anticancer investigations performed like, lung cancer cell A-549 culture, dye exclusion assay, MTT assay, morphological changes and compatibility with RBC, confirmed the presence of the moiety that have the cytotoxic and antiproliferative potential. Compatibility with RBC was observed, when treated with standard drug doxorubicin, and hydroalcoholic extract of C. inerme at 259.5 μg/ml concentration (IC50). In addition, the same treatment reveled, decrease in cytotoxic efficacy and cell viability against lung cancer cells. Furthermore, change in the cell morphology also suggesting potent antitumor properties of C. inerme. Dhaka Univ. J. Pharm. Sci. 17(2): 191-196, 2018 (December)